PERLINDUNGAN HUKUM BAGI ANAK NAKAL BERDASARKAN UNDANG-UNDANG SISTEM PERADILAN PIDANA ANAK - DWI PUTRI MELATI (KEADILAN PROGRESIF, 2018)
Increasing child delinquency, the need for legal protection for minors who commit illicit acts that need special handling. then the subject matter in this paper about the implementation of legal protection for children who are caught criminal acts based on the law of the criminal justice system of children. Problem approach using normative juridical approach (legal research). In practice the law on the criminal justice system of children prioritizes the restorative justice process using diversion. Law enforcers understand the special treatment of bad boys who commit illicit acts. Brats should be given understanding and education in order not to repeat negative actions again.